Epidemiology of status epilepticus in adults: A population‐based study on incidence, causes, and outcomes. (26th November 2018) - Leitinger, Markus; Trinka, Eugen; Giovannini, Giada; Zimmermann, Georg; Florea, Cristina; Rohracher, Alexandra; Kalss, Gudrun; Neuray, Caroline; Kreidenhuber, Rudolf; Höfler, Julia; Kuchukhidze, Giorgi; Granbichler, Claudia; et al.
Summary: Objective: In 2015, the International League Against Epilepsy (ILAE) proposed a new definition of status epilepticus (SE): 5 minutes of ongoing seizure activity to diagnose convulsive SE (CSE, ie, bilateral tonic–clonic SE) and 10 minutes for focal SE and absence SE, rather than the earlier criterion of 30 minutes. Based on semiology, several types of SE with prominent motor phenomena at any time (including CSE) were distinguished from those without (ie, nonconvulsive SE, NCSE). We present the first population‐based incidence study applying the new 2015 ILAE definition and classification of SE and report the impact of the evolution of semiology and level of consciousness (LOC) on outcome. Methods: We conducted a retrospective population‐based incidence study of all adult patients with SE residing in the city of Salzburg between January 2011 and December 2015. Patients with hypoxic encephalopathy were excluded. SE was defined and classified according to the ILAE 2015. Results: We identified 221 patients with a median age of 69 years (range 20‐99 years). The age‐ and sex‐adjusted incidence of a first episode of SE, NCSE, and SE with prominent motor phenomena (including CSE) was 36.1 (95% confidence interval [CI] 26.2‐48.5), 12.1 (95% CI 6.8‐20.0), and 24.0 (95% CI 16.0‐34.5; including CSE 15.8 [95% CI 9.4‐24.8]) per 100 000 adults per year, respectively. None of the patients whose SE ended with or consisted of only bilateral tonic–clonic activity died. In all other clinical presentations, case fatality was lower in awake patients (8.2%) compared with patients with impaired consciousness (33%). Significance: This first population‐based study using the ILAE 2015 definition and classification of SE found an increase of incidence of 10% compared to previous definitions. We also provide epidemiologic evidence that different patterns of status evolution and LOCs have strong prognostic implications.